Raqamli Kompetensiyani Rivojlantirishda O‘Qituvchilar Uchun Akt Va Media Savodxonlikni Integratsiyalashgan Yondashuv Asosida Shakllantirish Metodikasi - AKRAM O‘G‘LI, SA’DINOV AZIZBEK (Journal of Innovation in Education and Social Research, 2025)
This article explores the theoretical and methodological foundations for developing teachers’ digital competence through an integrated approach to enhancing ICT literacy and media literacy. In the context of educational digitalization, teachers are required not only to use technology, but also to analyze media content, ensure information security, follow digital ethics, and engage in professional reflection. The article justifies the need for integrating ICT and media literacy based on constructivist, competency-based, media-didactic and digital pedagogy approaches. The current state and needs of Uzbekistan’s education system are analyzed, and an integrated digital competence model for teachers is proposed. The findings indicate that a modular methodological approach to teacher training enables the simultaneous development of digital and media literacy and increases the effectiveness of teachers’ professional performance.